Dietary reference intakes for sodium and potassium - National Academies of Sciences, Engineering, and Medicine (U.S.). Committee to Review the Dietary Reference Intakes for Sodium and Potassium; Stallings, Virginia A.; Quirk, Meghan (Of the National Academies of Sciences, Engineering, and Medicine (U.S.)); Oria, Maria; National Academies of Sciences, Engineering, and Medicine (U.S.). Food and Nutrition Board (Washington, DC : The National Academies Press, 2019)
As essential nutrients, sodium and potassium contribute to the fundamentals of physiology and pathology of human health and disease. In clinical settings, these are two important blood electrolytes, are frequently measured and influence care decisions. Yet, blood electrolyte concentrations are usually not influenced by dietary intake, as kidney and hormone systems carefully regulate blood values. Over the years, increasing evidence suggests that sodium and potassium intake patterns of children and adults influence long-term population health mostly through complex relationships among dietary intake, blood pressure and cardiovascular health. The public health importance of understanding these relationships, based upon the best available evidence and establishing recommendations to support the development of population clinical practice guidelines and medical care of patients is clear. This report reviews evidence on the relationship between sodium and potassium intakes and indicators of adequacy, toxicity, and chronic disease. It updates the Dietary Reference Intakes (DRIs) using an expanded DRI model that includes consideration of chronic disease endpoints, and outlines research gaps to address the uncertainties identified in the process of deriving the reference values and evaluating public health implications.
Summary -- Introduction -- Applying the "Guiding Principles Report" -- Methodological considerations -- Potassium : dietary reference intakes for adequacy -- Potassium : dietary reference intakes for toxicity -- Potassium : dietary reference intakes based on chronic disease -- Potassium dietary reference intakes: risk characterization and special considerations for public health -- Sodium : dietary reference intakes for adequacy -- Sodium : dietary reference intakes for toxicity -- Dietary reference intakes based on chronic disease -- Sodium dietary reference intakes : risk characterization and special considerations for public health -- Knowledge gaps and future directions -- Appendixes
Includes bibliographical references.
This activity was supported by contracts between the National Academy of Sciences and the Centers for Disease Control and Prevention (Division for Heart Disease and Stroke Prevention), Food and Drug Administration (Center for Food Safety and Applied Nutrition), Health Canada (Health Products and Food Branch), National Institutes of Health (National Heart, Lung, and Blood Institute; National Institute of Diabetes and Digestive and Kidney Diseases; and Office of Dietary Supplements), Public Health Agency of Canada (Centre for Surveillance and Applied Research), and U.S. Department of Agriculture (Food and Nutrition Service). This activity was also supported in part by the National Academy of Sciences' W.K. Kellogg Foundation Fund and the National Academy of Medicine's Kellogg Health of the Public Fund. Any opinions, findings, conclusions, or recommendations expressed in this publication do not necessarily reflect the views of any organization or agency that provided support for the project.
Online resource; title from PDF title page (viewed January 8, 2020).
eBooks on EBSCOhost
Keywords: Cardiovascular system -- Diseases; Hypertension -- Risk assessment; Sodium in the body -- Research; Potassium in the body -- Research; Diet in disease -- Research; Chronic diseases -- Physiological aspects; Nutrition; Recommended Dietary Allowances; Sodium, Dietary; Potassium, Dietary; Nutritional Physiological Phenomena; Chronic Disease -- prevention & control; United States; Cardiovascular Diseases; Appareil cardiovasculaire -- Maladies; Hypertension artérielle -- Évaluation du risque; Sodium dans l'organisme -- Recherche; Potassium dans l'organisme -- Recherche; Régimes alimentaires -- Recherche; Maladies chroniques -- Aspect physiologique; Nutrition; Nutrition; Cardiovascular system -- Diseases; Diet in disease -- Research